Role of intrauterine tubo-peritoneal insemination and intrauterine insemination in the treatment of infertility - Gupta, Disha; Verma, Asha; Gupta, Richa; Saini, Soniya; Salvi, Anuradha; Meena, B. S. (International Journal of Research in Medical Sciences, 2017)
Background: Infertility management has become more substantial and relevant with an increase in the number of infertile patients as well as advances in the science of reproduction. The objective of our study was to assess the role of intrauterine tuboperitoneal insemination (IUTPI) and intrauterine insemination (IUI) in the treatment of infertile patients. Methods: 236 infertile patients, 118 in each group attending the infertility clinic, after applying both inclusion and exclusion criteria were enrolled in the present study. Patients in each study group were given clomiphene citrate for ovarian stimulation followed by injection hCG for triggering ovulation. Insemination with washed husband’s sperm was performed about 36-40 hours after hCG administration, using 10ml of inseminate in IUTPI and 0.5ml inseminate in IUI. The patient was then called after 2 weeks for urine pregnancy test (UPT) which, if positive was considered as clinical pregnancy. Results: Out of the total 236 cases, 42 cases had a positive outcome. Out of these 42 positive cases, 27 were from IUTPI group whereas 15 from IUI group. The pregnancy rate was 22.88% in IUTPI and 12.71% in IUI (p=0.039), which was a statistically significant difference. Endometrial thickness, preovulatory follicle number and prewash sperm motility significantly affected positive outcome in IUTPI. Factors like patient’s age, BMI<25, bilateral patent tubes and decreased duration of infertility also positively affected the treatment outcome. Conclusions: Our study found IUTPI to have better pregnancy rate compared to IUI. IUTPI may become a first line option for treatment of infertile patients.